2007
DOI: 10.1097/smj.0b013e31813c6a37
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Impact of Smoke-free Laws on Indoor Air Quality

Abstract: Smoke-free laws significantly impact indoor air quality. However, the temporal effects of these laws on indoor air pollution have not been determined. This paper assesses the temporal impact of one smoke-free law on indoor air quality. This quasi-experimental study compared the indoor air quality of nine hospitality venues and one bingo hall in Georgetown, Kentucky, before and after implementation of a 100% smoke-free workplace law. We made real-time measurements of particulate matter with 2.5 microm aerodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…The relationship between smoking density and indoor PM 2.5 level is shown in Figure 3 . The mean indoor PM 2.5 level was 333 m g/m 3 when more than one cigarette was The result was published in Lee et al (2007) . The result was published in Lee et al (2008) .…”
Section: Factors Associated With Indoor Fi Ne Particle Levelssupporting
confidence: 51%
See 2 more Smart Citations
“…The relationship between smoking density and indoor PM 2.5 level is shown in Figure 3 . The mean indoor PM 2.5 level was 333 m g/m 3 when more than one cigarette was The result was published in Lee et al (2007) . The result was published in Lee et al (2008) .…”
Section: Factors Associated With Indoor Fi Ne Particle Levelssupporting
confidence: 51%
“…The effect of smoke-free laws is not only significant but also immediate. In Georgetown, KY, indoor fi ne particle concentrations were immediately improved after the smoke-free air law ( Lee et al, 2007 ). These studies demonstrate that comprehensive smoke-free air laws reduce indoor air pollution to safe levels for workers and the public.…”
Section: Strength Of Smoke-free Air Laws and Indoor Air Qualitymentioning
confidence: 65%
See 1 more Smart Citation
“…22 In an indoor air quality study of Lexington hospitality venues, there was a 91% decline in fine particle air pollution after Lexington's smoke-free law went into effect. 23 Given that there is a positive association between outdoor air pollution and ED visits for asthma 24 among both children 25,26 and adults, 26,27 it is not surprising that there were fewer asthma ED visits in light of improved indoor air quality after Lexington's smoke-free law. Further study is needed to investigate the interactions among outdoor air pollution, smoke-free legislation, and asthma prevalence and health care outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…Major studies have shown that laws that ban smoking in public places such as bars and restaurants help improve the health of workers [24][25][26][27][28][29]. Additional studies conducted in several communities, states, regions, and countries have found that implementing comprehensive laws that make all workplaces and public places smoke-free are associated with rapid, substantial, and sustained reductions in emergency department visits for asthma and hospital admissions for heart attacks; these reductions appear to be more pronounced among nonsmokers than smokers [30,31].…”
Section: Gregory Sidebarmentioning
confidence: 99%